Analisis Pemanfaatan PLTS Pada Mesin Penanam Padi - Prames Wara Laksono Putra, Vogie; Cornelius Sarri; Toyib (PoliGrid, 2024)
Renewable energy is alternative energy Its availability is abundant in nature by a certain process sustainable and can be used for everyday life. One of the most frequently used uses is solar or solar thermal energy. Power plants Solar Energy (PLTS) is a form of realization of utilization solar energy itself. It is also possible to utilize solar energy used in the agricultural sector to help the community villages in farming, especially in rice cultivation. As for example, namely modernizing agricultural equipment, such as implementation solar cells in rice planters. This research was conducted for planning, designing and knowing the panel's capabilities solar to supply the DC motor load on the planting machine paddy. The results of this planning use 2 solar panels monocrystalline type with a capacity of 120 Wp connected in series, 2 batteries with a capacity of 12V 30Ah connected in series, solar charge controller with capacity of 12/24V 20A with a DC motor load of 250W. Based on the test results obtained conversion efficiency the largest solar energy is 35.2% while the efficiency is the smallest namely 11.51%. With the average panel energy conversion efficiency solar between 16.14% to 24.35%. And motor efficiency DC as the planter arm drive supplied by the system namely 91.02%. In this research it still has The disadvantage is that DC motors heat up easily when working driving the rice planter arm, this is because controlling the rotational speed of the resulting motor the voltage supplied does not comply with the DC motor specifications.